The Effect of Promotion Strategy and Product Quality on Customer Satisfaction Yan`s Coffee Kediri City - Agustina, Shinta; Zainal Arifin; Bayu Surindra (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to 1) determine the effect of promotional strategies on Yan's Coffee customer satisfaction 2) determine the effect of product quality on Yans's Coffee customer satisfaction. 3) determine the effect of promotional strategies and product quality on Yan's Coffee customer satisfaction. In this study using quantitative methods and quantitative sampling used in this study with random sampling of 86 samples. In the results of this study using the help of SPSS Version 23 with the results that the significance of the variables: 1) promotion strategy is 0.000 <0.05 or t count> t table 3,870> 1,662 which means H0 is rejected, so that the promotion strategy has an influence on customer satisfaction. 2) The meaning of product quality is 0.000> 0.05 or t count 3.520> 1.662, so H0 is rejected, which means that product quality has an influence on customer satisfaction 3) Promotional strategy and product quality simultaneously affect customer satisfaction with a total f of 38.571 significant 0.000, so H0 is rejected, which means that the promotional strategy variable and product quality have a simultaneous influence on the customer satisfaction variable.